Fabrication of CdS/PbS and CdS:Al/PbS solar cells: Optimization of the Al content in CdS and the solution pH during PbS deposition. (15th August 2021) - Rodríguez, C.A.; Mera, Adriana C.; Pizarro-Castillo, L.; Ashfaq, Mohammad; Sandoval-Paz, M.G.; Cortés Burgos, María Jose; Manidurai, Paulraj; Suárez, S.
Abstract: The CdS/PbS and CdS:Al/PbS thin film solar cells were fabricated using chemical bath deposition (CBD) process. The CdS thin film was deposited onto the ITO/glass substrate with different aluminum dopant concentration, whereas PbS layer was deposited over CdS thin film with different solution pH. The deposited CdS, CdS:Al and PbS thin films were characterized by scanning electron microscopy (SEM), Xray diffraction (XRD), diffuse reflectance spectroscopy (DRS), Rutherford Backscattered Spectroscopy (RBS) and Hall effect measurements. The results indicated that the aluminum concentration in CdS films reduces the crystallite size and increases the band gap and film resistivity. From PbS film characterization, it was obtained that increasing the solution pH the crystallite size augmented, meanwhile the band gap and electrical resistivity decreased. Photovoltaic characteristic performed to the different thin films solar cells, revealed that the highest conversion efficiency (ɳ %) 1.45% was observed in the bilayer system composed by a CdS layer doped with 9% of Al, and a PbS film grown at pH 10. Interestingly, CdS film with the highest resistivity and PbS with a medium band gap (1.48 eV) resulted in the highest conversion efficiency. Characterization of CdS, PbS and CdS/PbS samples suggested that the crystallite size, band gap and electrical resistivity were easily tuned with the help of CBD process that enhanced photo-conversion efficiency of the solar cells.